A new species of Pristimantis from southern Ecuador (Anura, Craugastoridae) - Szekely, P. (2016)
A new species of Pristimantis is described from Reserva Buenaventura, southern Ecuador, at elevations between 878 and 1082 m. A molecular phylogeny based on nuclear and mitochondrial genes shows that the new species is closely related to P. phoxocephalus, P. riveti, and P. versicolor. The new species differs from them and other morphologically similar congeners in having a low W-shaped dermal ridge in the scapular region, a large conical tubercle on the upper eyelid and on the heel, a thin mid dorsal fold, and a longitudinal lateral fold starting behind the tympanic fold and extending along the anterior two thirds of the flank. The new species inhabits cloud forests in the Pacific slopes of the Andes. © Paul Székely et al. This is an open access article distributed under the terms of the Creative Commons Attribution License.